Estruturas auto-construídas de B-caroteno e ácido octadecilfosfônico - Barbara Elza Nogueira de Faria (2016)
We investigated self-assembled structures of beta-carotene (B-carotene) via scanning probe microscopy. Initially, we deposited -carotene in solution on mica substrates and the formation of agglomerates was observed via atomic force microscopy (AFM). Then, new tests have been proposed to obtain self-assembled structures and we mixed this molecule with octadecylphosphonic acid (OPA: chemical formula C18H39O3P) in solution with different proportions and the AFM morphological characterization was repeated. We observed selfassembled monolayers with no phase separation in the samples which OPA was in higher proportion: 7 : 1, 5 : 1 and 3 : 1. The others, which B-carotene was in higher proportion, 1 : 7, 1 : 5 and 1 : 3, regions with small agglomerates and no organized structures have beenobserved. For a better understanding of which structures were formed in the proportions 7 : 1, 5 : 1 and 3 : 1, measurements of X-ray diffraction were carried out. Besides mica, we analyzed these systems in a nonpolar substrate, graphite. Differently from mica, which isa polar substrate, graphite proved to be a good substrate to get self-assembled structures of B-carotene. We observed higly organized structures of B-carotene in graphite via AFM in Peak Force mode. In the samples made by the mixing of these molecules, we also observedorganized structures of OPA+B-carotene, although with phase separation. Finally, preliminary tests via electric force microscopy were carried out in the samples of B-carot in graphite.